Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
[tex]\huge\color{pink}\boxed{\colorbox{black}{Answer ☘}}[/tex]
gívєn..
[tex]g(n) = - 2n - 4 \\ f(n) = 3n + 1[/tex]
lєt'ѕ ѕσlvє nσw~
[tex]g(n) \times f(n) = ( - 2n - 4)(3n + 1) \\ => -2n ( 3n + 1 ) -4 ( 3n + 1 ) \\ = > - 6n² - 2n - 12n - 4 \\ = > - 6n² - 14n - 4 \\ = > - (16n² + 14n + 4)[/tex]
hσpє hєlpful~
~вє вrαínlч!
Answer:
g(n) * f(n) = -6n² -14n - 4
Step-by-step explanation:
Given the following function operations g(n) * f(n), where: g(n) = -2n - 4, and f(n) = 3n + 1:
We can express the product of both functions as follows:
( g · f )(n) = g(n) · f(n) = (-2n -4)(3n + 1)
Next, use the FOIL method:
( g · f )(n) = (-2n -4)(3n + 1) = -6n² -2n - 12n - 4
Combine like terms:
( g · f )(n) = -6n² -14n - 4
Therefore, g(n) * f(n) = -6n² -14n - 4.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.